Первые сведения о нахождении в дальневосточных водах приапулиды галикриптус - (:unkn) unknown (My University, 1980)
Halicryptus spinulosus галикриптус, или игольчатый найден летом 1978 г. в литоральной зоне восточного Сахалина вблизи поселка Набиль. Регистрируется первая находка H. spinulosus в дальневосточных водах СССР.
The first information about finding of Halicryptus in the waters of the Soviet Far East
Halicryptus spinulosus is found in the intertidal zone near Nabil, East Sakhalin, in autumn, 1978. This is the first registered note of this species in the waters of the Soviet Far East.